Difference Between Empty Nest and Non-Empty Nest Rural Elderly in Bangladesh - Ety Rani (Universitas Djuanda, 2022)
This study has three objectives- to identify the socio-economic difference between the empty nest and non-empty nest rural elderly, to find out the difference between them based on their relationship with their children, and to differentiate the pattern of mental anxieties between them. The social survey method has been applied for data collection. For the empty-nest elderly, the researcher has selected three villages under the district of Jhenaidah. The non-empty-nest elderly researcher has established Shatoil village under the district of Naogaon. Data were collected from a total of 132 (100 non-empty-nest and 32 empty-nest) respondents using purposive sampling with informed consent. A semi-structured interview schedule was applied to collect the data. In this study, most empty-nest respondents' socio-economic conditions were satisfactory, but non-empty-nest respondents' socio-economic conditions were not. In both cases, the highest of the (empty-nest and non-empty-nest) respondents’ relationship with children was good and had no difference. The main difference between them is in the case of service providers. The greatest of the non-empty-nest elderly did not feel loneliness and mental anxieties. On the other hand, all the empty-nest respondents felt lonely and most suffered from mental anxietyanxieties. GOs and NGOs should build up adult recreation centers and old homes and train elders on using modern technology (such as Facebook, WhatsApp, Messenger, Skype, etc.) to communicate with children. It will mitigate their loneliness and mental anxiety